Barium Ferrites Loaded TiO2 Usage In Photocatalytic Degradation of Rhodamine B Under Visible Light - (:unkn) unknown (My University, 2017)
In the present study, the barium ferrites sample was synthesized by conventional citrate method as a first step, then it was used with different amounts in TiO2 synthesis via a soft hydrolysis method as a second step. Resulted photocatalyst samples were named as BaFts/TiO2. The samples were characterized by X-ray diffraction (XRD), UV–vis diffuse reflectance spectra (DRS) and scanning electron microscopy (SEM). The samples were tested in Rhodamine B degradation under visible light. Rhodamine B degradation efficiency was increased approximately 2.8 times with respect to the efficiency of the naked TiO2.

Bu çalışmada ilk basamakta baryum ferrit örneği klasik sitrat yöntemiyle sentezlenmiştir. İkinci basamakta bu örnek hidroliz yöntemi ile TiO2 sentezinde farklı miktarlarda kullanılmıştır. Elde edilen fotokatalizör örnekleri BaFts/TiO2 olarak adlandırılmıştır. Örnekler X-ışını difraksiyonu (XRD), UV-görünür alan difüz reflektansı (UV-vis DRS) ve taramalı elektron mikroskobu (SEM) ile karakterize edilmiştir. Örnekler, görünür ışık altında Rodamin B parçalanmasında kullanılmıştır. Rodamin B’nin parçalanma etkinliği, yalın TiO2’in etkinliğine kıyasla yaklaşık 2.8 kat artmıştır.
Görünür Işık Altında Rodamin B’nin Fotokatalitik Parçalanmasında Baryum Ferrit Yüklenmiş TiO2 Kullanılması
Keywords: Biyoloji; Mühendislik, Kimya